2015
DOI: 10.1007/s00405-015-3867-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cervical and ocular vestibular-evoked myogenic potentials in evaluation of benign paroxysmal positional vertigo of posterior semicircular canal

Abstract: Benign paroxysmal positional vertigo (BPPV) constitutes a major proportion of the population with peripheral vestibulopathies. Although the freely floating otoconia within the semicircular canals is responsible for the symptoms of BPPV, the source of the otoconia debris is mainly believed to be the otolith organs. Therefore, the pathology in either or both the otolith organs appears a logical proposition. Cervical and ocular vestibular-evoked myogenic potentials (cVEMP and oVEMP), being the tests for functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 55 publications
3
27
0
1
Order By: Relevance
“…The oVEMP being a utricular response, it could be useful in identifying utricular involvement in BPPV. This was indeed confirmed by the results of some of the recent studies that demonstrate utricular involvement in BPPV (Nakahara et al, 2013;Seo et al, 2013;Singh and Barman, 2015;Singh and Apeksha, 2016). While these studies reported reduced oVEMP amplitudes in the ears with BPPV, Seo et al (2013) and Singh and Barman (2015) also reported the finding of augmented oVEMP amplitude in the affected ears of individuals with BPPV.…”
supporting
confidence: 73%
“…The oVEMP being a utricular response, it could be useful in identifying utricular involvement in BPPV. This was indeed confirmed by the results of some of the recent studies that demonstrate utricular involvement in BPPV (Nakahara et al, 2013;Seo et al, 2013;Singh and Barman, 2015;Singh and Apeksha, 2016). While these studies reported reduced oVEMP amplitudes in the ears with BPPV, Seo et al (2013) and Singh and Barman (2015) also reported the finding of augmented oVEMP amplitude in the affected ears of individuals with BPPV.…”
supporting
confidence: 73%
“…This is a further testimony to the outcomes of phase I of the study which showed that 0.1-1000 Hz was a better band-pass filter than the 1-to 1000-Hz one and should, therefore, be considered optimum for clinical recording of oVEMP. Similar better response detection could be a probability in some of the individuals suffering from clinical conditions such as Meniere's disease or benign paroxysmal positional vertigo (BPPV), which are known to result in amplitude reduction of oVEMP or cause its absence in several cases (Singh and Barman, 2015;2016a,b;Singh and Apeksha, 2016), which, however, can be confirmed only after experimental evidence from future studies in this regard. Here, it would be important to mention a word of caution that two of 20 ears represent a small sample and require more controlled studies to further assert the findings.…”
Section: Phase II (Older Adults)mentioning
confidence: 92%
“…76,77 Similar results have also been reported for oVEMPs in the unaffected ear and for cVEMPs, suggesting that both sides and both otoliths may be affected by the same otoconial deterioration. Abnormality rates tend to be higher in oVEMPs than cVEMPs, 73,74 but AC oVEMPs are more sensitive to disease in general and recruitment bias is likely to be an important factor. In VN, patients with saccular dysfunction are less likely to present with BPPV, since this signifies involvement of the inferior division and thus posterior canal dysfunction, which would result in failure of dislodged otoconia to produce vertigo when they fall into the posterior canal.…”
Section: Benign Paroxysmal Positional Vertigomentioning
confidence: 97%
“…However, many studies have now demonstrated a higher than expected rate of VEMP abnormalities in patients with BPPV. 73,74 This is likely to occur for two reasons. First, some patients may develop BPPV following another vestibular disease (e.g., VN) or direct damage to the otoliths (e.g., head trauma).…”
Section: Benign Paroxysmal Positional Vertigomentioning
confidence: 99%
See 1 more Smart Citation